Efficiency and effectiveness of handling customer complain of Kentucky Fried Chicken from year 2005-2007 at Carpark Greenhills, San Juan City - Galam, Russel C. (Manila: National University, 2008)
The study sought to evaluate the handling of customer complain of KFC Carpark Greenhills towards the manager.
Chapter 1. The Problem and review of related literature -- Chapter 2. Review of related literature -- Chapter 3. Research methodology -- Chapter 4. Interpretation, presentation, and data analysis -- Chapter 5. Summary of finding, conclusions and recommendations
Includes bibliographical references.